Description of health patterns of fully vaccinated older adults hospitalized due to COVID-19 in Brazil through association rules (Research, Society and Development, 2022)
The coronavirus disease 2019 (COVID-19) is a global public health problem. Since the beginning of the pandemic, notified in March 2020, Brazil has shown high lethality from the disease in older adults. From 2012 to 2018, the country showed an increase of 20% in the older adults’ population. Despite the completeness of vaccine protocols against COVID-19 in the country, there is evidence that this age group, associated with the presence of comorbidities, can be a predictor of the occurrence of hospitalization and severe symptoms due to COVID-19. In this direction, this paper aimed to identify patterns and relationships between symptoms, comorbidities, gender, Intensive Care Unit (ICU) admission, and survival status of older adults, fully vaccinated against COVID-19, hospitalized in Brazil. For this purpose, we perform association rules mining on the OpenDataSUS database. For the group of patients with comorbidity, associations with conditions of oxygen saturation (SpO2)